1997
DOI: 10.1113/expphysiol.1997.sp004074
|View full text |Cite
|
Sign up to set email alerts
|

Glomerular haemodynamics during renal artery clamping and haemorrhage in the dog

Abstract: SUMMARYThe influence of a gradual decline in renal perfusion pressure (RPP) due either to renal artery clamping (C) or to haemorrhagic hypotension (HH) was studied using micropuncture techniques in anaesthetized dogs. The decrease in renal blood flow (RBF) was more profound and set in earlier during HH than during C, where perfect autoregulation was observed down to a mean arterial blood pressure of 85 mmHg. Glomerular filtration rate (GFR) was also only slightly decreased during C with no change in filtratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…We also found that in the 70-H group, circulating Cr levels were maintained within a normal range during the 3 hours of renal hypoperfusion 23 along with a continuous increase in CCr. These results are consistent with previous findings 24,25 that the glomerular filtration fraction can be elevated in response to hemorrhage to compensate for the decreased RBF. 24,25 Notably, such a "self-protecting" response of the kidney appears to be absent or overridden following a severe hemorrhage, as we found in the 55-H group that CCr was diminished along with a rapid accumulation of circulating Cr.…”
Section: Renal Tolerance To Hemorrhagic Hypotension Without Etsupporting
confidence: 93%
“…We also found that in the 70-H group, circulating Cr levels were maintained within a normal range during the 3 hours of renal hypoperfusion 23 along with a continuous increase in CCr. These results are consistent with previous findings 24,25 that the glomerular filtration fraction can be elevated in response to hemorrhage to compensate for the decreased RBF. 24,25 Notably, such a "self-protecting" response of the kidney appears to be absent or overridden following a severe hemorrhage, as we found in the 55-H group that CCr was diminished along with a rapid accumulation of circulating Cr.…”
Section: Renal Tolerance To Hemorrhagic Hypotension Without Etsupporting
confidence: 93%
“…Hypovolemia causes an increase in renal vascular resistance and decreases RBF and GFR, according to the tubuloglomerular feedback mechanism, observed in hemorrhage group pretreated with placebo. Heller and Horáček [ 38 ] observed earlier and more pronounced decrease in RBF and GFR after hypotension by hemorrhage than after clamping of the renal artery. They also observed that the sharp decline in RBF during hemorrhage was accompanied by a significant increase in RVR, from both the afferent and efferent arterioles.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reduced energetic efficiency of sodium transport in AKI means that even the reduced total reabsorption in AKI with reduced GFR may cause hypoxia (146). This may be further aggravated in hypovolemic states where predominant efferent arteriolar contraction means that filtration fraction is increased, leading to both relatively increased tubular load for reabsorption and reduced peritubular blood flow, thereby potentially worsening hypoxia (61). We have previously argued that blocking neurohormonal signaling like angiotensin II might reduce active reabsorption and protect the kidney from hypoxia during AKI (71); however, recent data show that the effect may be short lived as we cannot detect improved oxygenation after 1 wk of losartan treatment (115).…”
Section: Hypoxiamentioning
confidence: 99%